Implementasi Kebijakan Peraturan Menteri Kesehatan No 21 Tahun 2021 Tentang Persalinan Di Puskesmas Kecamatan Ngabang Kabupaten Landak - Endang Sulastri; Yulius Yohanes; Rupita Rupita (Jurnal Multidisiplin Dehasen (MUDE), 2026)
This study aims to analyze the implementation of the Minister of Health Regulation No. 21 of 2021 on Childbirth at the Ngabang Health Center, Landak Regency. This regulation is designed to improve the quality of childbirth services at health centers and ensure the safety of mothers and babies through the established procedures. Ngabang, being a border region, faces geographical and infrastructure challenges, which may affect the implementation of this policy.This research uses a qualitative approach with in-depth interviews with healthcare workers, the head of the health center, and the local community, as well as direct field observations. The results show that despite several challenges, such as the lack of trained medical personnel and limited facilities, this policy has had a positive impact on the quality of childbirth services. However, implementation still requires improvements in medical staff training, provision of adequate facilities, and increased community involvement. This study recommends further efforts to maximize support for policy implementation to achieve the goal of safe and quality childbirth services.